Applying social network analysis to support the management of cooperative project's behavioral risks - Nunes, Marco (2022)
According to several literature sources and bodies of practices, effective cooperation between organizations in the deliver of projects is a critical success factor for project successful outcome. Nevertheless, it seems that organizations are still reluctant to engage in cooperative networks more than it would be expected. The major reason for this - according to several literature sources - is due to a lack of efficient models to support organizational cooperative networks. This work introduces a model that contributes to the management of organizational cooperative networks, by adressing behavioral risks that usually emerge as organizations engage in cooperative networks to deliver projects. The proposed model was developed based on four key pillars ((1) project management, (2) risk management, (3) cooperative networks, and (4) social network analysis centrality metrics), and will analyze how four critical organizational cooperative informal networks ((1) trust, (2) problem-solving, (3) advice, and (4) communication), emerge and evolve throughout the different phases of a generic project lifecycle. The development and implementation of the proposed model is supported by a case study.